2016
DOI: 10.1179/2042618612y.0000000026
|View full text |Cite
|
Sign up to set email alerts
|

A normative study of cervical range of motion measures including the flexion–rotation test in asymptomatic children: side-to-side variability and pain provocation

Abstract: Objectives: Cervical movement impairment has been identified as a core component of cervicogenic headache evaluation. However, normal range of motion values in children has been investigated rarely and no study has reported such values for the flexion-rotation test (FRT). The purpose of this study was to identify normal values and side-to-side variation for cervical spine range of motion (ROM) and the FRT, in asymptomatic children aged 6-12 years. Another important purpose was to identify the presence of pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
8
1
1
Order By: Relevance
“…In our study, we found a significant reduction in NPRS for both rotations during the flexion-rotation test in the MT + E group. There is only one previous study that records NPRS during the flexion-rotation test [ 39 ], but the design of this study and the selection of the sample do not allow us to contrast our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we found a significant reduction in NPRS for both rotations during the flexion-rotation test in the MT + E group. There is only one previous study that records NPRS during the flexion-rotation test [ 39 ], but the design of this study and the selection of the sample do not allow us to contrast our results.…”
Section: Discussionmentioning
confidence: 99%
“…The movement stopped when either the subject presented symptoms, or the evaluator found a firm end feel, whichever situation occurred first [ 1 , 9 ]. If any pain appeared during the test, it was recorded by a verbal numeric pain rating scale (NPRS) (scale: 0 = no pain/ 10 = worst pain) for each rotation [ 39 ]. A Cervical Range of Motion (CROM) device (floating compass; Plastimo Airguide, Inc, Buffalo Groove, IL, USA) was used, and three measurements were taken for each rotation.…”
Section: Methodsmentioning
confidence: 99%
“…The flexion-rotation test for the upper cervical spine showed 52.97°(flexion-rotation right) and 52.38°(flexion-rotation left) ranging from 45°to 63°and 40°to 63°, respectively. 13 The Wilcoxon test for matched pairs to see if there was a statistically significant difference in the before and after measurements for active and passive ROM within the same patient for the side showing restriction at baseline compared to after treatment was done using SPSS version 21 (IBM Corp, Armonk, New York). Furthermore, the mean change scores for the 3 movements were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Restriction to the active spinal mobility in children with OI can be affected by changes in the bone structure and neck pain. Thus far, few studies have been conducted that would enable the creation of standards with division by age and sex for the mobility of individual joints in children [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%